HIV-1 Nucleic Acids Identify Rectal HIV Exposures in Self-Collected Rectal Swabs, Whereas Y-Chromosome Single Tandem Repeat Mixtures Are Not Reliable Biomarkers of Condomless Receptive Anal Intercourse. (1st October 2021) - Lemos, Maria P.; Nandi, Vijay; Dragavon, Joan; Fleming, Ira; Krishnan, Keertana; Musuruana, Martin; Kramer, Madeline; Glantz, Hayley; Andrasik, Michele; Coombs, Robert W.; McElrath, M. Juliana; Tieu, Hong-Van
Abstract : Background: To focus interventions, biomarkers of HIV-1 exposure could help in identifying subpopulations at highest risk of acquisition. We assessed whether Y-chromosome single tandem repeat (YSTR) mixtures obtained from rectal swabs could serve as a biomarker of condomless receptive anal intercourse (CRAI) among men who have sex with men and transgender women and evaluated the feasibility of detecting HIV-1 virions to assess exposures. Methods: Twenty-nine sexually active HIV-seronegative men who have sex with men and one transgender woman from New York City answered on-site and mobile app sexual behavior questionnaires. They were randomized to collecting self-administered rectal swabs every morning or after receptive anal intercourse (RAI). YSTR profiles were assessed from blood sample and swabs; HIV-1 exposure was measured by conducting quantitative polymerase chain reaction in swabs. Results: After 2 months, the daily mobile survey had 135%–201% more instances of anal sex acts and 170%–193% more RAI than on-site surveys. Daily mobile reporting had 11%–35% less CRAI events than those reported on-site ( P daily = 0.001; P per-sex = 0.047). The daily swabbing arm reported less RAI ( P < 0.001) and CRAI ( P < 0.038) and had 2.95 lower odds of detecting YSTR mixtures ( P = 0.021) than the per-sex-event arm. Surprisingly, YSTR detection was not significantly modified by report of bowel movements and lubricant, enema, or condom use. No participant became HIV-1 infected, yet HIV-1 total nucleic acids were detected in 6 independent episodes of CRAI in 2 participants taking pre-exposure prophylaxis. Conclusions: YSTR mixtures demonstrated 80% specificity but only 30% sensitivity as a biomarker of CRAI in self-collected rectal swabs. However, detection of HIV-1 exposures in self-collected swabs may help in identifying those needing further HIV risk reduction strategies. Abstract : Supplemental Digital Content is Available in the Text.